2015
DOI: 10.1016/j.ijdevneu.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sensitization between testosterone and cocaine in adolescent and adult rats

Abstract: Cocaine and anabolic-androgenic steroids are substances commonly co-abused. The use of anabolic steroids and cocaine has increased among adolescents. However, few studies investigated the consequences of the interaction between anabolic-androgenic steroids in animals' model of adolescence. We examined the effects of acute and repeated testosterone administration on cocaine-induced locomotor activity in adult and adolescent rats. Rats received ten once-daily subcutaneous (s.c.) injections of testosterone (10mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In our study, we observed cross-sensitization in adolescent, but not in adult rats. Our results corroborated our previous study showing cross-sensitization between testosterone and cocaine in adolescent, but not in adult rats ( 22 ). However, in that study we used different groups for adolescent and adult rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we observed cross-sensitization in adolescent, but not in adult rats. Our results corroborated our previous study showing cross-sensitization between testosterone and cocaine in adolescent, but not in adult rats ( 22 ). However, in that study we used different groups for adolescent and adult rats.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the importance, little is known about the effects of chronic testosterone administration on psychoactive substance behavior, including ATS. In fact, previous results from our laboratory showed that the chronic treatment with testosterone caused an increase in the cocaine stimulant effect in adolescent and adult rats, and locomotor cross-sensitization in adolescent rats ( 22 ). Therefore, a question to be answered is whether chronic testosterone use could promote cross-sensitization to amphetamine derivatives in adolescent and adult rats.…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, animal research has suggested that adolescents may be particularly sensitive to the effects of testosterone on reward systems. For instance, in rodent models, repeated administration of testosterone sensitizes adolescent male animals, but not adult males, to the locomotor effects of cocaine, a process that is dependent on changes in dopamine neurotransmission (Engi, Cruz, Crestani, & Planeta, 2015). Neuroendocrine research in animal models, therefore, has supported the possibility that gonadal hormone change will impact reward sensitivity and consequently sensation seeking.…”
Section: Are Developmental Differences In Reward Sensitivity and Sens...mentioning
confidence: 99%
“…Evidence suggests that dopamine is the substrate involved in this process (Kalivas and Stewart, 1991). Studies found that androgens like testosterone induce cross sensitization to cocaine in prepubertal, but not in adult male rats (Engi et al, 2015).…”
Section: Aas and Cocainementioning
confidence: 99%